Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada J&T Express Drop Center 08 Depok - Dwi Fuji Hastuti; Anisa Nurdina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study was to determine the effect of work discipline and work environment on employee performance at J&T Express Drop Center 08 Depok. The method used in this research is quantitative method. The population in this study were all employees as many as 56 respondents. The sampling technique in this study was saturated sampling technique or all members of the population were sampled. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis t test, and hypothesis f test. Thus H0 is rejected and H3 is accepted, meaning that there is a positive and significant influence between Work Discipline (X1) and Work Environment (X2) simultaneously on Employee Performance (Y) at J&T Express 08 Depok.